Second Trimester Cervical Ectopic Pregnancy and Hemorrhage: A Case Report and Review of the Literature - Jessian L. Munoz; Amanda Kalan; Katherine Singh (Hindawi Limited, 2018)
Cervical ectopic pregnancies are a rare occurrence in the United States. Here we present the interdisciplinary and conservative management approach to a cervical ectopic at an advanced gestational age. In addition, we review the surgical management of hemorrhage from cervical ectopic pregnancies, which is often catastrophic and life-threatening.